Progress of research on prevention and treatment of radiation-induced rectal injury in patients with pelvic malignancy (盆腔恶性肿瘤放疗所致放射性直肠损伤的防治研究进展) - LIU Na (刘娜); HAN Chengru (韩成如); LUAN Shunlian (栾顺莲) (中西医结合护理)
Radiation-induced rectal injury has a negative impact on the quality of life of patients with pelvic malignancy. This paper reviewed studies on pathogenetic mechanism, drug treatment and enema method for radiation-induced rectal injury, and provided reference for improvement of treatment efficacy and establishment of standardized treatment protocols. (盆腔恶性肿瘤患者接受放疗后引起的直肠放射性损伤会严重影响患者的生活质量。本文针对放射性直肠损伤的发生机制、国内外主要用药及灌肠方法的研究进展进行系统综述, 旨在为提高放射性直肠损伤的治疗效果和建立标准化治疗方案提供参考依据。)